2021
DOI: 10.1016/j.jadohealth.2021.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Do Conditional Cash Transfers Improve Mental Health? Evidence From Tanzania’s Governmental Social Protection Program

Abstract: Cash transfer interventions broadly improve the lives of the vulnerable, making them exceedingly popular. However, evidence of impacts on mental health is limited, particularly for conditional cash transfer (CCT) programs. We examined the impacts of Tanzania's government-run CCT program on depressive symptoms of youth aged 14e28. Methods: We utilized cluster randomized controlled trial data of 84 communities (48 intervention; 36 control). The intervention administered bimonthly CCTs to eligible households, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It is shown that both conditional and unconditional cash transfers weakly increase the dietary diversity; moreover, unconditional cash transfers weakly increase cognitive ability of children. Similarly, Prencipe et al (2021) find that conditional cash transfers in Tanzania decreased depressive symptoms among children.…”
Section: Related Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…It is shown that both conditional and unconditional cash transfers weakly increase the dietary diversity; moreover, unconditional cash transfers weakly increase cognitive ability of children. Similarly, Prencipe et al (2021) find that conditional cash transfers in Tanzania decreased depressive symptoms among children.…”
Section: Related Literaturementioning
confidence: 90%
“…Another strand of literature related to our paper uses experimental and quasi-experimental designs to study the impacts of social interventions on body weight and mental health outside the Western world. Prencipe et al (2021) , for example, focus on the impact of cash transfers on depressive symptoms of youth aged 14–28 in Tanzania. The meta-analysis by Durao et al (2020) examines how cash transfers help reducing food insecurity in low and middle income countries.…”
Section: Related Literaturementioning
confidence: 99%
“…More recently, research studies evaluating the impact of unconditional cash transfer programs in South Africa, Tanzania and Malawi found that unconditional cash transfers have stronger benefits for improving mental health, reducing symptoms of depression, and improving education and social support than conditional cash transfer programs (30)(31)(32). These are promising ways to address the socio-economic determinants of mental health, and highlight the importance of a multi-pronged approach to AMH research.…”
Section: Adolescent Mental Health Research and Intervention Developme...mentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, Zimmerman et al ( 8 ) found that while cash transfers may improve some mental health outcomes for children and young people, they had a null effect on depressive symptoms. Among studies carried out in Africa, impacts of cash transfers on depressive symptoms were largely heterogeneous, with differential effects by school enrollment ( 9 ), household wealth ( 10 ), and sex ( 11 , 12 ).…”
Section: Abbreviationsmentioning
confidence: 99%